The Use of Math Journey Learning Media to Optimize Student Collaboration Ability In Mathematics Learning Material Scales In Elementary Schools - Zaini, Rizky Amalia Dhiaul; Subrata, Heru (Tauladan Fathimah Azzahra, 2023)
This study aims to determine whether there is an impact on the use of Math Journey learning media in optimizing students' collaboration skills in learning mathematics on a scale material in elementary schools. This research is a type of quasi-experimental research or commonly called quasi-experimental research. Using the One-Group Pretest-Posttest Design. In this study, two variables will be measured, namely the independent variable Math Journey learning media, and the dependent variable student collaboration skills. The sampling technique used purposive sampling with a total sample taken of 25 students. The data collection instrument in this study used student collaboration skills assessment sheets. Data analysis techniques were calculated using a paired sample t-test using the SPSS 16.0 application. The results showed that the sig (2-tailed) value of 0.000 was less than 0.05. Thus, it can be concluded that there is a significant difference in student collaboration skills before and after being given treatment, namely an increase in student collaboration skills